HELLP Syndrome: Fetal Maternal Result. Maternal Intensive Care Unit Of The Perinatal Maternal National Institute - De-la-Peña-Meniz, Walter Jerry (2017)
Objective. Know clinical and pathological epidemiologic characteristics from HELLP Syndrome of admitted patients in the Maternal Intensive Care Unit from INMP. Materials and methods. Clinical histories from admitted patients in the Maternal Intensive Care Unit from INMP since August of 2014 to August 31st of 2016 were checked out. Furthermore, 502 records: 49 record of patients with HELLP Syndrome y 452 records of patients with preeclampsia diagnostic were included.